Effect of Bank-Specific Factors on Non-performing Loans Among Commercial Banks in Tanzania - George Thomas Budotela; Goodluck Mmarii; Nathaniel Towo (Universitas Syiah Kuala, 2022)
Objective –This paper examines the effect of bank-specific factors on non-performing loans in Tanzanian commercial banks (CBs).Design/methodology – Using annual data covering the period of 2011 -2020, a quantitative study methodology was employed. The authors used a one-step generalised method of moments (GMM) approach to estimate the effect of bank-specific factors on the percentage growth of NPLs in Tanzania.Results – According to the findings, increased return on assets, bank operating efficiency, income diversification, loan to-asset ratio in CBs reduces NPLs. In contrast, an increase in the deposit-to-asset ratio, capital adequacy, and age significantly increases the level of NPLs, which is consistent with the adverse selection theory. Conversely, decreased lag NPLs and raised bank operating efficiency will reduce the current year's NPL rate and vice versa.Research limitations/implications – Commercial banks should reduce the risk of defaulting borrowers by adjusting the contractual terms to the anticipated average quality of their applications. In addition, small banks should strive to maintain management efficiency to increase their profitability. Authorities should impose micro-prudential supervision on commercial banks' lending behaviour to reduce the number of NPLs.Novelty/Originality – The paper includes bank size (large and small banks) using both a one-step difference and a one-step system approach to measure the effect of bank-specific factors, which is usually not the case with most studies.